دور الإعلام الإسلامي في الدعوة والتوجيه برنامج مفاتيح في قناة القرآن الكريم نموذجا -دراسة تحليلية. - العطرة, ميداسي (University of Eloued جامعة الوادي, 2019)
" تعد هذه الدراسة من الدراسات التي تهدف إلى معرفة دور الإعلام في دعوة وتوجيه الافراد، وقد استهدفت الدراسة برنامج مفاتيح الذي يبث في قناة القرآن الكريم الجزائرية وقد تضمن البحث مقدمة وثلاثة فصول الفصل الأول عبارة عن إطار منهجي للبحث وتناولت فيه إشكالية وتساؤلات الدراسة، أهمية الدراسة، أهداف الدراسة، وأسباب اختيار الموضوع، تحديد المفاهيم والدراسات السابقة والمنهج المستخدم في هذه الدراسة، وهو المنهج الوصفي المسحي لتحليل المحتوى ام عينة الدراسة فكانت من ثلاثة أشهر (جانفي، فيفري، مارس) لسنة 2019، ثلاثة حصص لكل شهر عدا شهر مارس فكانت حصتين فقط، ومدة بث البرنامج ساعة ونصف بمعدل كل الحصص 712دقيقة وفي الفصل الثاني : تناولت الدراسة الأسس النظرية للعملية الإعلامية، فكان مدخل إلى الاعلام الإسلامي، وفي المبحث الثاني الإعلام الإسلامي ودوره الدعوي أما ثالثا ذكر الفرق بين الدعوة الإسلامية والعمل الإعلامي والمبحث الأخير تعريف التلفزيون والبرامج التلفزيونية. أما الفصل التطبيقي تم التطرق فيه للتعريف بقناة القرآن الكريم وبرنامج مفاتيح ومقدميه ثم التحليل الخاص بمضمون وشكل البرنامج، والخاتمة فيها ملخص ما توصلت اليه الدراسة خلال التحليل اما النتائج المتوصل اليها كانت كالآتي: - الإعلام الإسلامي هو الاعلام الذي يسير وفق مبادئ وضوابط مصدرها الكتاب والسنة وتزويد الناس بالأخبار الصحيحة. - الدعوة هي النداء للطرف الأخر سوى كان مسلما او غيره لتباع أوامر الله واجتناب نواهيه . -ركز برنامج مفاتيح على الموضوعات الشرعية واعتمد في الاستشهاد على القرآن الكريم، واستخدم اللغة العربية الفصحى في مخاطبة المشاهدين بمختلف مستوياتهم لأنها اللغة الانسب لإيصال المعلومة وإحداث التغيير . " "This study is one of the studies aimed at knowing the role of the media in inviting and guiding individuals. The study aimed at the keys program which is broadcast in the channel of the Holy Quran in Algeria. The research included an introduction and the first three chapters of the first chapter. It is a systematic framework for research. The study, the reasons for selecting the subject, the definition of concepts and previous studies and the methodology used in this study, the descriptive descriptive method of analyzing the content or the sample of the study was three months (January, February, March) for the year 2019, three quotas for each month except March, were only 2 hours of the program for one hour and a half at a rate of 712 minutes. In the second chapter, the study dealt with the theoretical basis of the media process. It was an introduction to the Islamic media, and in the second part, the Islamic media and its role. The third was the difference between the Islamic call and the media work. As for the applied chapter, we discussed the definition of the Quran channel, the program of keys and its providers, and then the analysis of the content and form of the program. The conclusion of the study was summarized in the analysis. The results reached were as follows: -Islamic media is the media that follows the principles and disciplines originating from the Quran and Sunnah and provide people with the right news. -The call is to appeal to the other party, except to be Muslim or others to buy the orders of God and avoid his intentions. -The program focused on the subjects of legitimacy and was adopted in the martyrdom of the Koran, and used the standard Arabic language in addressing the audience at various levels because it is the language most appropriate for the delivery of information and change "
مذكرة ماستر تخصص دعوة واعلام
Keywords: الوسائل، الإعلام ,الإعلام الإسلامي, الدعوة .: media, Islamic media, advocacy.